1996
DOI: 10.1016/0895-7061(95)00353-3
|View full text |Cite
|
Sign up to set email alerts
|

A Telecommunications System for Monitoring and Counseling Patients With Hypertension Impact on Medication Adherence and Blood Pressure Control

Abstract: This study was conducted to evaluate the effect of automated telephone patient monitoring and counseling on patient adherence to antihypertensive medications and on blood pressure control. A randomized controlled trial was conducted in 29 greater Boston communities. The study subjects were 267 patients recruited from community sites who were >or= 60 years of age, on antihypertensive medication, with a systolic blood pressure (SBP) of >or= 160 mm Hg and/or a diastolic blood pressure (DBP) of >or= 90 mm Hg. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
317
2
27

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(353 citation statements)
references
References 20 publications
7
317
2
27
Order By: Relevance
“…A direct positive effect of TBPM on BP control has been previously reported, 27 probably due to an optimized compliance. 28,29 The greater number of measurements during dosage titration gives the physician a higher certainty to act on. This was confirmed by the change of dosages after the 2nd ABPM.…”
Section: Discussionmentioning
confidence: 99%
“…A direct positive effect of TBPM on BP control has been previously reported, 27 probably due to an optimized compliance. 28,29 The greater number of measurements during dosage titration gives the physician a higher certainty to act on. This was confirmed by the change of dosages after the 2nd ABPM.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit limited in number, previous randomized controlled studies 8,16,17 have shown a beneficial effect of telemedical monitoring on blood pressure control. In 1996, Friedman et al 8 found that when hypertensive patients used a telephone-linked computer system to report their HBP, diastolic blood pressure decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 8,16,17 have suggested a beneficial effect of telemedical monitoring on blood pressure control. However, to our knowledge, no study in a typical primary care setting has compared the accuracy of the conventional CBP with that of HBP, using a memory-equipped device with telemedical transmission capabilities.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…When coupled with dedicated solutions for instrument data transmission, CTI can also provide patients with feedback on their care. Several successful CTI applications have been tested in different medical problems, with particular reference to chronic patient's care [36]. Clearly, CTI alone may limit the applicability of the system, and should be always associated with Web based solutions for data access by the health care providers and patients themselves.…”
Section: Multi-access Ser6icesmentioning
confidence: 99%